Distributed Network for Health Diagnosis Using Blockchain for Early Analysis and Detection of Health Aliment’s - Balakrishna, Sunil; Parvathy L, Rama (International Journal of Engineering and Technology, 2018)
Information technology plays very important role in the healthcare sector and as new technology are introduced the potential of those technologies are tried out to see how better the healthcare sector could get advantage of these new technologies. From the time of internet age, the healthcare sector has undergone massive changes and with new technologies like Cloud Computing has bought enormous possibilities in having Personal Health Record (PHR) management. One of such latest technology which has been successfullytested and getting introduced is Blockchain. The growing interest in utilizing this technology into Health Sector especially for PHR due to its disturbed network model and the security design it has embedded in it.Â